The Effect of Stunting Early Detection (STULYTION) Website on The Level of Knowledge of Balanced Nutrition in Mothers Aged 12-59 Months at Kebonarum Klaten Health Center - Firma, Brigita Senanda Septia; Istikhomah, Henik; Suryani, Emy (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2025)
Background : Children under five are children aged 12 - 59 months In Indonesia, the prevalence of stunting is expected to be 21.6% in 2022.Maternal knowledge is the factors influencing nutritional needs fulfillment behavior among children under 5 years of age..Stunting Early Detection (Stulytion) Website is a website developed by researchers that contains information that can affect the level of knowledge of balanced nutrition of toddler mothers which later can also contribute to improving the fulfillment of nutrition for their toddlers.Objective : To determine the Effect of Stunting Early Deetection (Stulytion) Website on the Level of Knowledge of Balanced Nutrition in Mothers of Toddlers Aged 12-59 Months at the Kebonarum Klaten Health CenterMethod : This research is a type of quantitative research using a one group pre-test post-test design. The sampling technique with the cluster sampling method obtained the number of respondents 83 mothers of toddlers aged 12-59 months. The data analysis technique used Wilcoxon's non-parametric statistics with a significance level of 0.05.Result : There is an influence of the Stunting Early Detection (Stulytion) Website on the level of knowledge of mothers of toddlers aged 12-59 months at the Kebonarum Klaten Health Center with a p value of 0.000 (p < 0.05).Conclusion : There is an influence of the Stunting Early Detection (Stulytion) Website on the level of knowledge of mothers of toddlers aged 12-59 months at the Kebonarum Klaten Health Center.